Implementation of rights for crime victims in theory and practice : lessons from India - Sharma, Anupama (Law teacher) (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"There are many different ways in which victims' rights can be implemented. The implementation pattern may vary depending on the type of rights a jurisdiction offers and the purposes it seeks to achieve via these rights. However, there are a few basic aspects that remain common to the variation in the implementation patterns across jurisdictions. This book provides a theoretical and practical overview of such implementation patterns, their features and underlying differences. It presents theoretical models capturing the different types of implementations of victims' rights and the purposes that they can achieve. The book also offers a framework comprising of the essential aspects involved in implementation of rights such as drafting and presentation, their visibility and accessibility to victims, enforcement of rights in case of breach, assessment and evaluation of rights to ensure constant monitoring and improvement in implementation. The framework is tested by a sample case study in New Delhi, India which showcases how the framework can be moulded and applied to assess the existing implementation of victims' rights and the scope for reform. The book will be of interest to those working in the areas of Criminal Justice, Criminal Procedure, Victimology and Human Rights"--
Exploring Purposes of Victims' Rights -- Theoretical Modelling of Victims' Rights and Fulfilment of Purposes -- Indicators constituting the implementation of victims' rights -- Empirical Analysis based on the Commitment Indicator -- Empirical Analysis based on the Actionability Indicator -- Empirical Analysis based on the Assessment Indicator.
Keywords: Victims of crimes -- Legal status, laws, etc. -- India; Reparation (Criminal justice) -- India; LAW / Criminal Procedure; SOCIAL SCIENCE / Criminology; LAW / Civil Rights